A preclinical study of allogeneic CD19 chimeric antigen receptor double‐negative T cells as an off‐the‐shelf immunotherapy drug against B‐cell malignancies - Dan Wang; Liuyang Wang; Shuai Liu; Jianjun Tong; Honglin Zhu; Man Xu; Xiancai Li; Zhiqiang Xiang; Qinghua Sun; Hengcai Wang; Yuli Wang; Shuyang Wang; et al. (Clinical & Translational Immunology)
Abstract Objectives To evaluate the manufacturability, efficacy and safety of allogeneic CD19 chimeric antigen receptor double‐negative T cells (CD19‐CAR‐DNTs) as an off‐the‐shelf therapeutic cell product. Methods A membrane proteome array was used to assess the off‐target binding of CD19‐CAR. DNTs derived from healthy donors were transduced with lentiviral vectors encoding the CD19‐CAR. The manufacture of the CD19‐CAR‐DNTs was under GMP conditions, and their surface molecule expression patterns were characterised using flow cytometry. We investigated the off‐the‐shelf potential of CD19‐CAR‐DNTs by evaluating the cryopreserved CD19‐CAR‐DNTs in terms of cell viability as well as their cytotoxicity against various CD19+ target cell lines and primary patient blasts in vitro. We evaluated the persistence and safety of the cryopreserved CD19‐CAR‐DNTs in xenograft models in vivo. Results GMP‐grade CD19‐CAR‐DNTs were manufactured and cryopreserved for use in advance. The cryopreserved CD19‐CAR‐DNTs maintain their viability and antitumor activity against various CD19+ target cell lines and primary patient blasts. These cells significantly prolonged the survival in Raji‐Luc‐xenografted NOG mice. Multiple infusions of the cells can further augment their efficacy. Remarkably, following a single infusion in mice, CD19‐CAR‐DNTs rapidly got distributed among well‐perfused organs initially, and progressively spread to most tissues, peaking at Day 43. In toxicity studies, CD19‐CAR‐DNTs significantly reduced tumor burden and ameliorated tissue damage in tumor‐bearing NOG mice. Critically, no immunotoxicity or graft versus host disease was observed in non‐tumor‐bearing NOG mice. Conclusions The allogeneic CD19‐CAR‐DNTs fulfil the requirements of an off‐the‐shelf therapeutic cell product, offering a promising new approach to the treatment of haematological malignancies.